Evidence‐based guideline: Neuromuscular ultrasound for the diagnosis of ulnar neuropathy at the elbow. Issue 2 (17th December 2021) - Shook, Steven J.; Ginsberg, Matthew; Narayanaswami, Pushpa; Beekman, Roy; Dubin, Andrew H.; Katirji, Bashar; Swaminathan, Bharathi; Werner, Robert A.; Cartwright, Michael S.
Abstract: Introduction/Aims: The purpose of this literature review is to develop an evidence‐based guideline for the use of neuromuscular ultrasound in the diagnosis of ulnar neuropathy at the elbow (UNE). The proposed research question was: "In patients with suspected UNE, does ulnar nerve enlargement as measured with ultrasound accurately identify those patients with UNE?" Methods: A systematic review and meta‐analysis was performed, and studies were classified according to American Academy of Neurology criteria for rating articles for diagnostic accuracy. Results: Based on Class I evidence in four studies, it is probable that neuromuscular ultrasound measurement of the ulnar nerve at the elbow, either of diameter or cross‐sectional area (CSA), is accurate for the diagnosis of UNE. Recommendation: For patients with symptoms and signs suggestive of ulnar neuropathy, clinicians should offer ultrasonographic measurement of ulnar nerve cross‐sectional area or diameter to confirm the diagnosis and localize the site of compression (Level B).